2011
DOI: 10.1111/j.1460-2466.2011.01565.x
|View full text |Cite
|
Sign up to set email alerts
|

Young Voters' Responses to the 2004 U.S. Presidential Election: Social Identity, Perceived Media Influence, and Behavioral Outcomes

Abstract: Hostile news perceptions, perceived media influence, and behavioral outcomes among Republicans and Democrats were examined before and after the 2004 U.S. presidential election. Predictions were grounded in social identity/self-categorization theories, and influence of presumed influence. Hostile news perceptions were greater among Republicans, especially Fox News viewers. Third-person perceptions (TPPs) for ingroup and outgroup (own party, other party) varied based on media message (debates, news, spin, polls,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…Although this may boost ratings, scholars have found that viewers are more likely to distrust political institutions after watching conflict-ridden programming (Forgette & Morris, 2006) and that Republican FOX News viewers are more likely to perceive the media as hostile than Democratic viewers (Hoffner & Rehkoff, 2011). In research conducted on outrage discourse, Sobieraj and Berry (2011) found that conservative media was much more likely than liberal media to use outrage tactics and elicit a "visceral response from the audience" (p. 19).…”
Section: Hostility and Confrontation Newsmentioning
confidence: 99%
“…Although this may boost ratings, scholars have found that viewers are more likely to distrust political institutions after watching conflict-ridden programming (Forgette & Morris, 2006) and that Republican FOX News viewers are more likely to perceive the media as hostile than Democratic viewers (Hoffner & Rehkoff, 2011). In research conducted on outrage discourse, Sobieraj and Berry (2011) found that conservative media was much more likely than liberal media to use outrage tactics and elicit a "visceral response from the audience" (p. 19).…”
Section: Hostility and Confrontation Newsmentioning
confidence: 99%
“…Other cognitive factors that can explain self-other discrepancies are: ego involvement (Perloff, 1989) or self-perceived knowledge (Atwood 1994;Peiser & Peter 2000. Age, gender and group identity (Hoffner & Rehkoff 2011) or education (Paul, Salwen, & Dupagne 2000), can also be good predictor variables of TPE.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the suggested psychological processes underlying TPE are optimistic bias (Gunther and Mundy, 1993;Salwen and Dupagne, 2003), ego involvement (Perloff, 1989), and social comparison (Atwood, 1994). Social distance (Brosius and Engel, 1996), education (Paul et al, 2000), age, gender, racial group, and group identity (Hoffner and Rehkoff, 2011) have been shown as factors that impact on the TPE discrepancy.…”
Section: The Perceived Influence Of Media Contentmentioning
confidence: 99%
“…In this sense, studies of the TPE behavioural component have mainly focused on the support to ban or censor controversial content, such as explicit sexual content (Gunther, 1995), misogynistic songs (McLeod et al, 1997), unfair and misleading political messages (Hoffner and Rehkoff, 2011), and trash talk-shows (GuerreroSolé et al, 2014). Even though censorship is associated with authoritarian societies, citizens in democratic societies express their willingness to censor specific controversial media content if it is perceived as socially harmful (McLeod et al, 2001).…”
Section: The Perceived Influence Of Media Contentmentioning
confidence: 99%